HIRA PADA PEKERJA WELDING DAN GRINDING BENGKEL LAMBUNG UTARA DI PT. DOK DAN PERKAPALAN SURABAYA (PERSERO) - Devin Sandiaji Putri (JURNAL PENELITIAN KESEHATAN, 2016)
HIRA (Hazard Identification and Risk Analysis) is the part of risk analysis’s process which aim to knowing potential hazards and risks belonging to the job.  The purpose of this research is to do hazard identification and risk analysis at the north hull workshop PT. Dok dan Perkapalan Surabaya (Persero) welding and grinding’s workers.This research is an observational research which is a cross sectional research based on the time of the research. The object of this research was concerned on north hull workshop PT. Dok dan Perkapalan Surabaya (Persero), with all engine room’s crew as population. Primary data obtained through observation, questionnaires and interview that were presented in the table form, diagram, and analyzed descriptively.The result of this research showed that north hull workshop PT. Dok dan Perkapalan Surabaya (Persero) there were 14 activities, 28 hazards and risks.  7 hazards are belong to high risk level, 14 hazards as medium risk and the rest 7 hazards as low risk level. Thus hazards which are categorized as high level risks or unacceptable hazards can be downgraded into low risk level or acceptable hazards.Keyword: grinding, hazard identification, risk assessment, welding.